Mathematical Models of Pressure and Microdisplacement Sensors Based on Electric Field Perturbation of the Surface Acoustic Waves - M.F. Zhovnir; O.O. Oliinyk; L.D. Pysarenko (Журнал нано- та електронної фізики)
The paper describes the functional charts, mathematical models and metrological parameters estimation of microdisplacements and pressure sensors on the basis of the electric field perturbation of the surface acoustic waves (SAW), which are distributed on the surface of a piezoelectric